Beauty Factory : planning a future in a slow economy - Payne, Herb (SAGE Knowledge. Cases., 2017)
Le-Sel Research, a family-owned, South African manufacturer of beauty products, launched Beauty Factory in 2011, after seeing a gap for affordable, high-quality beauty products. As a boutique retailer of beauty and home products, the brand had achieved early success, but growth and profitability had faltered as the economy had weakened. The marketing team believed that the brand had great potential. However, the challenge was to ensure that it reached its potential amidst the changing market conditions. Andrew Frodsham, the owner and CEO of Le-Sel Research, was considering a radical shift in strategy from selling only through its branded Beauty Factory outlets to selling through some or all of the big retail chains in South Africa. In early 2014, he met with his team to map out the future of Beauty Factory.